(untitled) (Ameghiniana, 2014)
Two fossil woods ofLauraceae are described from the Upper Pleistocene in the province of Entre Ríos, Argentina. The description of these taxa are based on anatomically preserved stems. The presence of the following combination of features distinguishes the Lauraceae from other dicotyledonous families: a) diffuse porous wood; b) vessels predominantly solitary with a tendency for short, radial multiples; e) crowded alternate intervascular pitting; d) heterocellular rays, mostly I to 3 cells wide; e) paratracheal vasicentric parenchyma; and f) presence of idioblasts. Comparisons show that Ulminium mucilaginosum n. sp. and Ulminium artabeae n. sp. are different from other fossil species of the Lauraceae.